Numerical methods with MATLAB : a resource for scientists and engineers - Borse, Garold J. (Boston, MA : PWS, 1997)
Linear analysis and matrices. MATLAB applied to functions of a single variable. Functions of two or more variables. Data analysis and modeling. Differential equations. Programming in MATLAB.
Keywords: Matlab; Data processing; Numerical analysis; Numerical analysis -- Data processing; MATLAB